2021
DOI: 10.1016/j.jhepr.2020.100193
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived thrombospondin 1 promotes obesity-associated non-alcoholic fatty liver disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
0
36
1
Order By: Relevance
“…Consistently, a previous study showed that SMPDL3B modulates insulin receptor signaling and thereby contributes to the production of ceramide-1-phosphate ( Fornoni et al, 2014 ; Mallela et al, 2019 ; Mitrofanova et al, 2019 ). Moreover, macrophage-derived thrombospondin 1 promotes obesity-associated non-alcoholic fatty liver disease through suppressing the expression of SMPDL3B ( Gwag et al, 2021 ). Together, these results indicated that SMPDL3B may regulate starch and sucrose metabolism via modulating insulin signaling in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a previous study showed that SMPDL3B modulates insulin receptor signaling and thereby contributes to the production of ceramide-1-phosphate ( Fornoni et al, 2014 ; Mallela et al, 2019 ; Mitrofanova et al, 2019 ). Moreover, macrophage-derived thrombospondin 1 promotes obesity-associated non-alcoholic fatty liver disease through suppressing the expression of SMPDL3B ( Gwag et al, 2021 ). Together, these results indicated that SMPDL3B may regulate starch and sucrose metabolism via modulating insulin signaling in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…TSP-1 deletion in adipocytes does not protect mice from diet-induced NAFLD/NASH, whereas myeloid/macrophagespecific TSP-1 deletion protects mice against liver injury. Autocrine-acting macrophagederived TSP-1 suppresses SMPDL3B expression, thereby increasing TLR4-mediated proinflammatory signaling and promoting NAFLD progression [121]. Recently, BMP-1 was shown to be an activator of TSP-1 and an agonist of TGF-β signaling [122].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Autocrine-acting macrophage-derived TSP-1 suppresses SMPDL3B expression, thereby increasing Toll-like receptor 4-mediated proinflammatory signalling and promoting NAFLD progression. 121 Recently, BMP-1 was shown to be an activator of TSP-1 and an agonist of TGF-β signalling. 122 Besides acting as a vital regulator of TGF-β activation, TSP also has TGF-β independent biological functions, e.g.…”
Section: Activation Of Tgf-β Signalling Ligands From Ecm Storagementioning
confidence: 99%
“…Blocking macrophage scavenger receptor 1 (MSR1) in vitro reduced saturated fatty acid-induced inflammatory gene expression in primary MFs and in vivo administration of an anti-MSR1 antibody ameliorated liver inflammation in a NAFLD mouse model [ 155 , 180 ]. Thrombospondin-1 (TSP1) can induce pro-inflammatory gene expression in MFs and MF-specific TSP1 −/− mice showed reduced liver injury in experimental NAFLD, suggesting MF-specific TSP1-modulation as a therapeutic strategy [ 196 ]. Various other targets have been proposed in NAFLD, of which their in vivo ameliorating effects are reported to be mediated by modulating inflammatory gene expression in MFs, including glucocorticoid-induced leucine zipper [ 197 ], hypoxia-inducible factor 1α [ 198 , 199 , 200 ], vitamin D receptor [ 201 ], farnesoid X receptor [ 202 ] and peroxisome proliferator-activated receptors (PPARs) [ 185 ].…”
Section: Macrophages During Gut-liver Axis Disruption In Chronic Liver Diseasementioning
confidence: 99%